2016
DOI: 10.1097/dad.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Epidermotropic B-Cell Lymphoma

Abstract: Epidermotropic B-cell lymphoma represents a subset of marginal zone lymphoma characterized by a papulosquamous rash most frequently resembling pityriasis rosea, occurring almost exclusively in older males. We speculate that aberrant expression of CXCR3 in marginal zone lymphoma of the skin is associated with migration of lymphoma cells to the epidermis and could lead to an epidermotropic pattern given the known role of CXCR3 expression in neoplastic T cells in the localization of mycosis fungoides to the epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Interestingly, epidermotropic MZL often presents as a papulosquamous eruption that mimics pityriasis rosea, albeit with a more protracted course (eg, months to years). 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, epidermotropic MZL often presents as a papulosquamous eruption that mimics pityriasis rosea, albeit with a more protracted course (eg, months to years). 3 …”
Section: Discussionmentioning
confidence: 99%
“…The immunophenotypic profile of epidermotropic MZL displays immunohistochemical positivity for the B-cell markers CD20, CD79a, and PAX but does not stain for follicle center markers, such as BCL6 and CD10, or T-cell markers, such as CD3. 3 Importantly, by histopathology alone, the diagnosis of epidermotropic MZL may be difficult to establish, as it frequently exhibits a low-power architecture that can be easily mistaken for T-cell lymphoproliferative disorders such as MF, based on the superficial bandlike array of inflammatory infiltrate and significant epidermotropism. 3 In these settings, immunohistochemical staining for B-cell markers represents an indispensable diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a novel form of immune escape in advanced cutaneous T cell lymphoma. Additional cutaneous lymphomas/leukaemias have also reported expression of the CXCR3 receptor on tumor cells including in epidermotrophic B cell lymphoma, lymphomatoid papulosis and skin lesions of leukemic plasmacytoid dendritic cell neoplasms ( 129 131 ).…”
Section: Introductionmentioning
confidence: 99%
“…XCR1 surface protein was found to be significantly elevated in DLBCL cases manifesting in the bone marrow [174] and also present in the majority of extranodal DLBCL cases [173]. CXCR3 protein expression was higher in thyroid DLBCL than stomach DLBCL [175] and has also been observed in case reports of epidermotropic B cell lymphoma [176] and intravascular large B cell lymphoma [177]. Closely related primary mediastinal large B-cell lymphomas (PMBCLs or MLBCLs) have been characterized by increased CCR9 and decreased CCR6, CCR7 and CXCR5 immunoreactivity compared to nonmediastinal DLBCL [14, 178].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 93%
“…CXCR3 is strongly expressed on the surface of the majority of MZLs and was identified via IHC in 14/14 (100%) patients with splenic MZL, 15/16 (94%) patients with extranodal MZL [4] and 5/5 (100%) cases of epidermotropic MZL [176]. One study found that only 13% of cutaneous MZLs were CXCR3-positive compared to 85% of other extranodal MZLs implying that CXCR3-negative patients comprise a unique subtype of MZL [189].…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%